Unusual open-system behaviour revealed by LA-MC-ICP-MS U–Th dating of coral and coralline algae bio-carbonates - Condomines, Michel; Bruguier, Olivier; Hajji, Inès; Zaara-Ben Mosbah, Chedia (Comptes Rendus. Géoscience)
This paper presents new U–Th ages obtained by LA-MC-CP-MS (laser ablation - multi-collector - inductively coupled plasma - mass spectrometry) on coral samples from a sedimentary core of the Tunis lagoon. The ages and calculated ($^{234}$U/$^{238}$U)$_{0}$ initial ratios, similar to the seawater value for most corals demonstrate that they behaved as closed systems, or with only a very limited loss of $^{234}$U and $^{230}$Th. The ages (from 196 to 182 ka) show that the coral-rich sediments were deposited near the end of isotope stage 7. The precision on the dates is comparable to those of alpha-spectrometry (around 7.6% on average), but the possibility of multiple in-situ analyses offers other advantages. An example is provided by the very unusual open-system behaviour found in the outer Mg-calcite border of a coral branch, formed by a coralline red alga. The very high ($^{234}$U/$^{238}$U) and ($^{230}$Th/$^{238}$U) activity ratios (1.41 and 2.04, respectively) are tentatively explained using the model proposed by [Thompson et al., 2003], that involves continuous enrichment of $^{234}$Th ($^{234}$U) and $^{230}$Th recoil nuclei provided by an U-enriched source. We suggest that this source might come from the bio-mineral itself, in the form of organic matter originally involved in the encrusting algal activity, and eventually degraded with an almost complete U-loss.